1883 Wash. Sess. Laws 102 An Act for the Protection of Fish and Game, § 12. - (:unkn) unknown (General Publisher, 1883)
Every person who shall use any sink box on any lake or river, or other waters in Washington Territory, for the purpose of shooting ducks or geese or other water fowls therefrom, or who shall use any batteries or swivel or pivot gun on boats, canvas, rafts or other device at any time, for the purpose of killing any water fowl within the limits of Washington Territory, shall be guilty of a misdemeanor.
--
Keywords: HUNTING REGULATION